Research on floating body resistance characteristics of floating photovoltaic and analysis of influencing factors - Wang, Hao; Liu, Xiaolei; Wang, Kan (Frontiers in Marine Science, 2024)
The floating structure of floating photovoltaic can be attached by aquatic organisms, resulting in changes in the draft depth of the floating body, which can affect the resistance characteristics of the floating body at different water velocities. The analysis for the characteristics of flow field is the key to revealing the change law of resistance under different conditions. The k-ε turbulence model which has been verified by water channel experiment is used to research the influence of draft depths, velocities and number of floating bodies for the drag in the paper. The research results show that the draft depth has more influence on the drag of the single floating body than on the velocity of water flow. The main reason is that the separation of the boundary layer produces a larger separation bubble, which increases the pressure difference between the front and back surfaces of the floating body, leading to a larger entrainment range and reflux velocity in the wake. The high flow velocity will enlarge the influence of the draft depth on the drag. The shielding effect of the tandem floating bodies is reflected in the non-uniform fluctuation of velocity and pressure along the flow direction, which affects the wake development of the tandem floating bodies, resulting in the typical spatial characteristics of resistance at different positions. The increase of the number of tandem floating bodies will further expand the difference of flow field, which can affect the resistance distribution law. The research results can provide theoretical support for the stability design of floating photovoltaic.